Sustainability of Productive Waqf as an Instrument of Sharia Economic Law to Support the Achievement of SDGs - Ghefira Nur Fatimah; Muthoifin; Widjiono Purnomo (Walidem Institute and Publishing, 2025)
Objective: The purpose of this study is to examine the position of productive waqf as an instrument in Sharia economic law, in a relevant way for the achievement of the SDGs in Indonesia. There is an analysis of the conception and implementation of productive waqf management. This research intends to be an expansion to be more effective in advancing through the contribution of the community to reach the sustainable development goals of productive waqf from the SDGs. Theoretical framework: Islamic philanthropic theory focuses on productive waqf as a social instrument for prosperity. The theory of sustainable development can be exploited to study the contribution of productive waqf to reach the role of the SDGs, and there are challenges and regulations from many considerations in managing waqf in Indonesia in terms of legal, economic, and even social aspects in optimizing waqf. Literature review: This literature review includes literature that examines the background of Sharia economic law and its constant expansion. In terms of research, it is also stated that waqf has a contribution with great potential in the fields of health, education, and the advancement of SMEs. From another perspective, examining the recognition in the form of challenges in waqf management to advance effectively and transparently in organizing in Indonesia. Methods: For this study, qualitative methods and a literature review were used. Data collection is through a review of studies in the form of articles, as well as reports related to productive waqf and SDGs. The elaboration is by recognizing the concepts, as well as challenges in waqf management, and conveying them as recommendations for the continuation of moving forward. Results: The great potential of productive waqf to contribute to reaching the SDGs in Indonesia, by prioritizing health, education, and expansion for SMEs. In the challenges of society, there is a lack of understanding and regulations, weak and not optimal. There needs to be transparency and consolidation of regulations for sustainability. Novelty: the novelty of this research focuses on productive waqf to provide solutions to waqf management challenges, as well as observing in the form of participation to reach the SDGs in Indonesia, and supporting insights to use waqf according to a sustainable economy.